Regeneration of Cartilaginous Tissue After Transplantation of Allofibroblasts - A. B. Tilyakov; B. A. Magrupov; M. D. Urazmetova; B. R. Karimov; B. S. Ubaydullaev; V. Kh. Sharipova (Общая реаниматология, 2016)
Aim of investigation. To prove the usefulness of the use of embryonic fibroblasts for the regeneration of cartilaginous tissue.Material and methods. New experimental model of symphysis pubis rupture followed by its recovery was employed in 24 male Shinshilla rabbits (2.3—3.5 kg body mass) in 3 series of experiments. In the first series, reconstruction was not employed. In the 2nd series, the reconstruction of symphisis was performed with the aid of tantal wired cerclage (d=1.2 mm). In the 3d series, the reconstitution was the same as in the previous series of experiments with addition of grown embrional allofibroblast tissue pieces. Duration of experiments was 7, 14, 21and 30 days. After each experiment, pieces of cartilaginous tissue were fixed with 10% neutral formalin and embedded in paraffin. Histological sections were stained with hematoxylin, eosin and VanGieson. Results. After the rupture of symphysis pubis of the pelvic bone, the cartilaginous tissue undergone alterations followed by formation of chondromatous nodules of different sizes and sclerosis of surrounding muscular and osseous tissues. In the second series of experiment after pelvis symphysis pubis rupture and symphysis recovery with the help of cerclage, the morphologic investigation revealed the formation of mixed initial callus consisting of connective and chondromatous tissue elements. In the third series of experiment it has been shown that within 4 weeks of experiment, the connective tissue with intensive basophil stain is formed in the area of symphysis pubisrupture. Connective tissue formation in surrounding soft tissue structures was associated with the formation of cartilaginous cells.Conclusion. Process of formation of cartilaginous tissue in the area of symphysis pubis rupture as evident by the experimental observation demonstrates the stimulating influence of allogeneic fibroblasts on process of cartilaginous tissue regeneration that ensures premises for clinical development of suggested method of regeneration.